Jak Walijczycy reformują swoją oświatę? - Janina Zawadowska (Problemy Wczesnej Edukacji)
The article contains a description of the experience of the representatives of the Federation of Educational Initiatives and the Association for the Development of Educational Initiatives at a study visit in Wales which took place in October 2008 under the European Programme Leonardo da Vinci, project: “New ideas in rural education: A Small School and a Small Kindergarten”. Its aim was to familiarize the participants with the process of introduction of a reform of education which had been initiated by the drafting of a document “Wales: the Learning Country”. My comments are on the planned changes in methods, core curriculum, and teacher education (for example, Trinity College in Carmarthen).